Laxative effects and mechanism of action of Brazilian green propolis - Kakino Mamoru; Izuta Hiroshi; Tsuruma Kazuhiro; Araki Yoko; Shimazawa Masamitsu; Ichihara Kenji; Hara Hideaki (BMC, 2012)
Abstract Background Brazilian green propolis is reported to have wide range of biological properties including antibacterial, anti-inflammatory, anti-influenza, and antioxidant activities. In the digestive system, a protective effect of propolis on gastric ulcer has been reported, but a laxative effect has not yet been reported. We investigated the effect and the mechanism of action of water and ethanol extracts of Brazilian green propolis. Methods We examined the laxative effect of propolis on stool frequency by administering orally an ethanol extract of propolis (EEP) or a water extract of propolis (WEP) at 10, 50, 100, or 500 mg/kg to normal mice. We then investigated the effects of propolis using constipation model mice induced by two types of drugs, loperamide (a μ opioid receptor agonist) and clonidine (an α-2 adrenergic receptor agonist). We also investigated the effects of WEP on gastrointestinal transit and contractional tension of the ileum to uncover the mechanism of action of WEP. Results Treatment with WEP, but not with EEP, significantly increased the weight of stools (p<0.01 at 500 mg/kg). WEP treatment significantly restored stool frequency and stool weight in clonidine-induced constipation model mice, but not in loperamide-induced constipation model mice. WEP treatment did not affect gastro-intestinal transit, but significantly increased the contractional tension of the isolated ileum of guinea pigs. This increase was inhibited by an acetylcholine receptor antagonist (atropine), but not by a 5-HT receptor antagonist (GR113808). Conclusion These findings indicate that WEP has laxative effects both in normal mice and in clonidine-induced constipation model mice. The laxative effects of WEP might be mediated by increased contractional tension of the ileum exerted at least in part via activation of an acetylcholine receptor.